Kota Kata Kita #3: Interpret the City Through the Perspective of the Performing Arts - Warsana, Dedi -; Supiarza, Hery -; Pauhrizi, Erik Muhammad; Sarbeni, Irwan (Gelar: Jurnal Seni Budaya, 2022)
This study discusses the Dramaturgy lecture process using a direct acting practice approach in a theater performance project where the city is positioned as object material, then interpreted and articulated by students through the process of creating theatrical performances. The creation process went through collaborative learning from research on cities, script writing, to creation of works, while Dramaturgy is placed as a theoretical approach in theater creation. This research is an effort to provide empirical experience to students in creating teamwork as a basis for film and television work patterns. This study uses a participatory action research method where the author is involved in all actions taken by film and television (FTV) students. This study found that through project: 1) students gain an understanding of dramaturgy as a science of analyzing drama with all kinds of derivatives related to it, 2) it is more effective to gain empirical experience as a real provision when creating film and Television works, 3) students can create works based on real cases. This research is expected to be able to strengthen KBK in FTV study program and become a treasure trove of intellectual property particularly in Universitas Pendidikan Indonesia and generally become a strategy for developing dramaturgy learning for Indonesia Society